2022
DOI: 10.1590/fst.72020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical, nutritional, and organoleptic properties of nuggets based on moringa (Moringa oleifera) leaves and giant catfish (Arius thalassinus)

Abstract: This study aimed to evaluate the physicochemical, nutritional, and organoleptic properties of nuggets based on Moringa oleifera leaves and Arius thalassinus. The ratio of the giant catfish and M. oleifera leaves were 100:0, 100:5, 100:10, and 100:15. The increase of M. oleifera leaves affected the characteristics of nugget products, viz., texture profile, protein, amino acids, cooking loss, and water holding capacity (WHC). Based on sensory tests, the four types of giant catfish nuggets with M. oleifera leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
14
0
5
Order By: Relevance
“…Analisis kimia yang dilakukan yaitu kadar air, kadar abu, kadar lemak dan karbohydrat bydifferent menggunakan metode AOAC (AOAC, 2004). Analisis kadar protein dilakukan menggunakan metode DuMaster Buchi D-480 dengan DuMas combustion (Solichah et al, 2021). Analisa mineral magnesium (Mg) dan kalsium (Ca) dianalisa menggunakan flame Atomic Absorption Spectrometric (AAS) tipe GBC 933AA (Minantyo et al, 2019).…”
Section: Karakteristik Kimiaunclassified
See 1 more Smart Citation
“…Analisis kimia yang dilakukan yaitu kadar air, kadar abu, kadar lemak dan karbohydrat bydifferent menggunakan metode AOAC (AOAC, 2004). Analisis kadar protein dilakukan menggunakan metode DuMaster Buchi D-480 dengan DuMas combustion (Solichah et al, 2021). Analisa mineral magnesium (Mg) dan kalsium (Ca) dianalisa menggunakan flame Atomic Absorption Spectrometric (AAS) tipe GBC 933AA (Minantyo et al, 2019).…”
Section: Karakteristik Kimiaunclassified
“…Pengujian dilakukan dengan 5 parameter penilaian meliputi warna, rasa, aroma, tekstur dan penerimaan secara keseluruhan. Skor penilaian yang digunakan terdiri dari 5 tingkatan yaitu sangat suka (5), agak suka (4), suka (3), agak tidak suka (2), dan tidak suka (1) (Solichah et al, 2021).…”
Section: Karakteristik Organoleptikunclassified
“…In addition, children asked more nuggets after given a nugget of 50 grams This means that children really like mushroom variant catfish nuggets. Study of Solichah et al [9] revealed that sensory tests results found the insignificant different of four types of giant catfish nuggets with M. oleifera leaves. Giant catfish nuggets and moringa leaves have the potential of being developed into products that can be consumed widely.…”
Section: Resultsmentioning
confidence: 97%
“…2019). Penambahan daun kelor pada nuget ikan lele k mempenaruhi sifat fisikokimia, kandungan protein dan tekstur nuget ikan lele (Solichah et. al.…”
Section: Pembahasanunclassified